Hepatic alveolar hydatid disease (Echinococcus multilocularis), a mimic of liver malignancy: a review for the radiologist in non-endemic areas. Issue 4 (April 2019) - Chouhan, M.D.; Wiley, E.; Chiodini, P.L.; Amin, Z.
Abstract : Alveolar hydatid disease or alveolar echinococcosis (AE) is caused by the parasite Echinococcus multilocularis and is increasingly seen as an imported disease in non-endemic areas such as the UK. It is rare compared to cystic echinococcosis (CE), but like CE commonly affects the liver. AE does have imaging features that can aid in diagnosis, but is often initially misdiagnosed as liver malignancy. It is usually fatal if untreated, underscoring the importance of early diagnosis. This review highlights the role of imaging in AE diagnosis with the broader objective of increasing radiologists' awareness of this unusual, but increasingly prevalent disease.